DESIGNING VALUE INTEGRATED LESSON PLANS: DESIGNING VALUE INTEGRATED LESSON PLANS - Hasibuan, Kalayo; Choirunnisyak; Julianida, Elsa; Faturrahman, Farhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRAK The integration of values into lesson plans has become increasingly important in modern education because schools are expected not only to improve students’ academic achievement but also to develop their character, morality, and social responsibility. This literature review aims to explore the concept of designing value integrated lesson plans, identify strategies for integrating values into classroom instruction, and examine the challenges and benefits discussed in previous studies. This study employs a narrative literature review method by analyzing relevant articles and educational publications from databases such as Google Scholar, ERIC, and Scopus. The findings indicate that value integration commonly includes moral, religious, social, and environmental values, while effective implementation strategies involve discussion-based learning, project based learning, reflective activities, and storytelling. The review also reveals several challenges, including limited teacher training, lack of instructional guidance, and difficulties in assessing value-based learning outcomes. Despite these challenges, the literature consistently demonstrates that value-integrated lesson plans contribute positively to students’ character development, engagement, collaboration, and critical thinking skills. In conclusion, designing value-integrated lesson plans plays an important role in creating meaningful and holistic learning experiences, and this review suggests the need for stronger support from teachers, curriculum developers, and future research regarding practical implementation and assessment methods.